Mobile Augmented Reality for Hearing Impaired Museum Engagement (MARHIME): a conceptual model - Baker, Esraa Jaffar; Abu Bakar, Juliana Aida; Zulkifli, Abdul Nasir (IP Publishing LLC, 2018)
Most Mobile Augmented Reality (MAR) applications for museum are largely tailored for normal visitors while the disabled such as hearing-impaired (HI) visitors are not well supported. This makes them to go through unpalatable experiences and eventually dissatisfy with their visit to the museum. In order to attract HI museum visitors’ interest, our study employs the concept of engagement through the use of the MAR application. Our recent finding revealed several MAR elements for museum HI visitors’ engagement. These elements include aesthetics, curiosity, usability, interaction, motivation, satisfaction, self-efficacy, perceived control, enjoyment, focused attention and interest. These elements which were extracted from a comprehensive literature review are then validated through expert reviews. A total of eleven elements were sent for review by the experts and they have validated six elements of engagement. This paper proposes a conceptual model of MAR for HI museum engagement (MARHIME).This model is expected to provide guidelines for developers in developing MAR applications that are able to engage HI museum visitors and make them satisfy with the museum visit. Our future work will develop the MARHIME application which will be validated by HI museum visitors.